Perencanaan Pajak, Beban Pajak Tangguhan dan Manajemen Laba Pada Perusahaan Non Manufaktur - Rahman, Arief; Al Hamzah, Muhammad Habibie; Novitasari, Dita Dwi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to determine the effect of tax planning and deferred tax burden on earnings management listed on the Indonesia Stock Exchange (IDX). The independent variables in this study are Tax Planning and Deferred Tax Burden. At the same time, the dependent variable in this study is Earnings Management. The population in this study consisted of non-manufacturing banking sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period, totaling 47 companies. The method of determining the research sample used purposive sampling. Based on the established criteria, the number of samples obtained was 38 companies, and the number of observations was 114. The study results show that partial tax planning and deferred tax burden have a significant effect on earnings management. In contrast, simultaneously, tax planning and deferred tax burden also have a significant effect on earnings management.